Transformasi Digital dalam Praktik Auditing: Tantangan, Peluang, dan Implikasi terhadap Kualitas Audit di Era Big data - Nirwana, Ema; Permana, Didik (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
Digital transformation has fundamentally reshaped auditing practices, particularly through the integration of technologies such as Artificial Intelligence (AI), big data, and blockchain. This study aims to identify the challenges, opportunities, and implications of digital transformation on audit quality in the big data era. A qualitative descriptive approach was employed, using case studies and simulations as the primary methods of analysis. The findings reveal that digitalization contributes positively to audit quality by enhancing time efficiency, testing accuracy, and risk detection capabilities. Nevertheless, challenges such as technological resource limitations, the need for auditor skill development, and ethical and data security risks remain significant barriers. This study highlights the urgency of developing a holistic digital audit framework and updating regulatory standards to ensure sustainable digital transformation. Recommendations are provided for practitioners, regulators, educational institutions, and scholars to collaborate in building an adaptive, professional, and ethical auditing ecosystem in the digital era.